Hubungan Antara kualitas Pelayanan Dengan Tingkat Kepuasan Konsumen Di Rumah Makan Awan Bengi Kartasura - Dwi Cita, Putri, Rusdin Rauf, STP., M.P, Endang Nur W,SST.,M.Si Med (2016)
Introduction: The restaurant is a place of business that serves the guests who come to the scope of its activities to provide food and drinks were of a commercial nature. The rapid development of the restaurant business, the increasing competition in the field.One effort in maintaining consumer kualiats yitu to provide good service. The main factors affecting the quality of service is a service that customers expect (expected service) and perception of the service (perceived service). Objective: To determine the relationship between consumer satisfaction with the quality of services at Rumah Makan Awan bengi. Methods: This study is a quantitative descriptive data analysis techniques used in this study is the correlation of Spearman. Results: This study done on 30 respondents, based on the characteristics of sex that most respondents were female gender as many as 18 (60%), and most respondents aged 20-29 years were 19 respondents (63.4%). Quality of service with sufficient category were 17 respondents (56.7%), consumer satisfaction with the category are satisfied as much as 24 respondents (80%). Based on the test results indicate sparman corelasi value of 0,981, and the p-value (0.000) <0.05 means that there is a significant relationship kulaitas service to customer satisfaction. Conclusion: based on the results of the study concluded the quality of service with enough categories, consumer satisfaction with the category are satisfied and there is a significant relationship kulaitas service to customer satisfaction.